1999
DOI: 10.1017/s0012162299001280
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral style of young boys with fragile X syndrome

Abstract: To study the behavioral style or temperament of 45 boys, aged 47 to 88 months, with full-mutation fragile X syndrome (FXS), 102 parent ratings on the Behavioral Style Questionnaire (McDevitt and Carey 1978) were recorded. These ratings were analysed with a variety of statistical techniques. Considerable variability was evident in temperament profiles; consequently, a characteristic profile was not identified for FXS. Boys with FXS differed significantly from the reference sample on five of nine temperament dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Based on previous characterizations of temperament in children with ASD using Thomas and Chess’ model (Bailey, et al, 2000; Bieberich & Morgan, 2004; Garon et al, 2009; Hatton, et al, 1999; Hepburn & Stone, 2006), we hypothesized that the ASD group would be more active, more withdrawn, less adaptive, less intense in their reactions, and less sensitive to environmental stimuli compared to the typically developing group. It also was expected that the ASD group would be more withdrawn on the approach dimension compared to the DD group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on previous characterizations of temperament in children with ASD using Thomas and Chess’ model (Bailey, et al, 2000; Bieberich & Morgan, 2004; Garon et al, 2009; Hatton, et al, 1999; Hepburn & Stone, 2006), we hypothesized that the ASD group would be more active, more withdrawn, less adaptive, less intense in their reactions, and less sensitive to environmental stimuli compared to the typically developing group. It also was expected that the ASD group would be more withdrawn on the approach dimension compared to the DD group.…”
Section: Discussionmentioning
confidence: 99%
“…Given this inherent conceptual overlap, it is not surprising that previous studies have found that the temperament profiles for children with ASD, as a group, differ from that of typically developing (TD) children (Bailey et al, 2000; Bieberich & Morgan, 2004; Garon et al, 2009; Hatton et al, 1999; Hepburn & Stone, 2006). Compared to TD comparison groups, children with ASD were more active, more withdrawn (Bailey et al, 2000; Bieberich & Morgan, 2004; Garon et al, 2009), less adaptive (Bailey et al, 2000; Hepburn & Stone, 2006), less persistent (Bailey et al, 2000), less intense in their reactions (Hatton et al, 1999), less sensitive to environmental stimuli (Hepburn & Stone, 2006), and had lower positive affect, higher negative affect, and more difficulty controlling attention and behavior (Garon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Levels of temperament have been shown to remain relatively stable in FXS across early childhood (Hatton, et al). Compared to typical controls, parents have indicated elevated activity and withdrawal; as well as lower intensity, approachability, adaptability, sadness, anger, and persistence in young boys with FXS (Bailey et al 2000; Hatton et al 1999; Roberts et al 2006; Shanahan et al 2008). Evidence suggests that temperament does not differ across participants FXS+autism and FXS-only (Bailey et al 2000); however, dampened facial sadness has been associated with autistic symptoms in FXS (Shanahan et al).…”
Section: Introductionmentioning
confidence: 97%